1994
DOI: 10.1300/j013v21n04_06
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Predictors of College Women's Body Image Attitudes

Abstract: African-American and Euro-American women from three predominantly Euro-American colleges in the southeast U.S. between 17 and 23 years of age completed instruments assessing body image attitudes, social competence, sex-role attitudes, racial identity, and a measure of family and personal characteristics. Analyses revealed race differences on all body image measures with the exception of appearance evaluation which was influenced by family income and race. Specifically, African-American women reported more sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 9 publications
3
81
1
Order By: Relevance
“…Indeed, racial/ethnic variations in women's body image and endorsement of gender-typed traits (Harris, 1994;Myers, 1989) are reasons to suspect that any effect of sport participation on self-esteem could vary across populations and that our findings may not be at all "normative" for Women of Color. 2 Thus, future researchers might strive to oversample participants from minority groups and to treat the diverse racial/ethnic and socioeconomic backgrounds of study participants as integral to model building rather than simply assuming that a middle-class cultural context represents the norm for all young women.…”
Section: Limitations Of the Present Researchmentioning
confidence: 91%
“…Indeed, racial/ethnic variations in women's body image and endorsement of gender-typed traits (Harris, 1994;Myers, 1989) are reasons to suspect that any effect of sport participation on self-esteem could vary across populations and that our findings may not be at all "normative" for Women of Color. 2 Thus, future researchers might strive to oversample participants from minority groups and to treat the diverse racial/ethnic and socioeconomic backgrounds of study participants as integral to model building rather than simply assuming that a middle-class cultural context represents the norm for all young women.…”
Section: Limitations Of the Present Researchmentioning
confidence: 91%
“…Some research suggests that, among African Americans, the ideal body size is larger than among European Americans and that size is less salient in judging attractiveness (Harris, Walters, & Waschull, 1991;Powell & Kahn, 1995). Two studies of men and women (Gray, 1977;Harris et al, 1991) and three of women only (Abrams, Allen, & Gray, 1993;Akan & Grilo, 1995;Harris, 1994) have found African American college students to have a more positive body image than the White students. Although the majority of research to date has examined women, some studies have indicated that European American men tend to be significantly more dissatisfied with their body weight than Black men (Gray et al, 1987;Harris et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the current literature has focused almost exclusively on body satisfaction and perceptions of ideal bodies and has neglected behavioral and affective components of body image. For example, only three studies included assessments of appearance investment (Harris, 1994;Miller et al, 2000;Smith et al, 1999), defined as the perceived importance of appearance, and documented the frequency of appearance-related behaviors (Cash, Thériault, & Annis, 2004). Of these studies, only one employed a non-college sample and included European Americans and African Americans (Smith et al, 1999).…”
mentioning
confidence: 99%